Perbezaan leksikal dan semantik berita bola sepak antara media Sepanyol dan Argentina / Mahadhir Mat Lazim - Mahadhir, Mat Lazim (2011)
This study that adopts the comparational analysis method was aimed to look into the scenario of football news language usage in Spanish and Argentinian media. Three printed media for each country were selected based on their physical circulation statistics, while the analyzed corpus was obtained from their online versions. Marca.com, As.com and MundoDeportivo.com were chosen for Spanish side while Ole.Clarin.com, Clarin.com and LaNacion.com for Argentina. Through intertext differences, the lexical and semantical differences patterns were investigated and were found to be of nine types of differences: different words but with same meanings, similar words used in both variants but with different meanings, similar words but with interference of semantic components, words without a semantic match in the other variant, words with different level of usage tendency in the other variant, words that are alternative in own variant but are the main choices in the other variant, institutional differences, syntactically different words and morphologically different words. Findings and conclusion are expected to increase understandings of investigators and speakers of Spanish from the aspects of lexical and semantical diversity that beautify the language. Although mutual intelligibility is high between both countries, national identity building is the factor that adds to the beauty and diversity of Spanish at international stage.